Development of an Integrated GIS - Spatial Model for Water Quality Assessment of Lake Maryout, Alexandria, Egypt - Ismail, Ismail Youssef; Mohamed, Soha A. (جامعة المنوفية - كلية الآداب - مركز البحوث الجغرافية والكارتوجرافية, 2019)
Lake Maryoutis one of Egypt’s Northern Lakes facing the Mediterranean Sea. It is considered the most polluted basin in Egypt as it suffers from pollution due to discharging the contaminated drainage water, untreated domestic, agricultural and industrial wastes.lt is one of the “hot spots” in Alexandria and constitutes a major source of pollution to the Mediterranean Sea through El-Max Bay. The severe pollution of the Lake caused a deterioration of the water quality of the lake, especially in its main basin. Lake Maryout suffers from pollution, reduction of its surface area, unplanned development in a way that considerable part of the lake entered into possible irreversible processes. The purpose of this study is to assess the degree of pollution in the context of WQI (Water Quality Index) in Maryout Lake by determining various physicochemical parameters, such as the temperature, salinity, COD, BOD, CHL-a, NO2, NO3, and NH3.
Keywords: البحيرات -- جودة المياه -- التلوث المائي -- الاستشعار عن بعد -- نظم المعلومات الجغرافية -- بحيرة مريوط -- محافظة الإسكندرية -- مصر